Critical Solvation Structures Arrested Active Molecules for Reversible Zn Electrochemistry - Zhang, Junjie; Zhang, Bao; Chen, Xin; Hao, Wenyu; Yao, Jia; Li, Jingying; Gan, Yi; Wang, Xiaofang; Liu, Xingtai; Wu, Ziang; Liu, Youwei; Lv, Lin; et al. (Nano-Micro Letters, 2024)
Aqueous Zn-ion batteries (AZIBs) have attracted increasing attention in next-generation energy storage systems due to their high safety and economic. Unfortunately, the side reactions, dendrites and hydrogen evolution effects at the zinc anode interface in aqueous electrolytes seriously hinder the application of aqueous zinc-ion batteries. Here, we report a critical solvation strategy to achieve reversible zinc electrochemistry by introducing a small polar molecule acetonitrile to form a “catcher” to arrest active molecules (bound water molecules). The stable solvation structure of [Zn(H2O)6]2+ is capable of maintaining and completely inhibiting free water molecules. When [Zn(H2O)6]2+ is partially desolvated in the Helmholtz outer layer, the separated active molecules will be arrested by the “catcher” formed by the strong hydrogen bond N–H bond, ensuring the stable desolvation of Zn2+. The Zn||Zn symmetric battery can stably cycle for 2250 h at 1 mAh cm−2, Zn||V6O13 full battery achieved a capacity retention rate of 99.2% after 10,000 cycles at 10 A g−1. This paper proposes a novel critical solvation strategy that paves the route for the construction of high-performance AZIBs. Highlights: 1 Critical solvation structure changes the hydrogen bond network through “catchers”. 2 Catcher further arrests the active molecules to promote Zn2+ deposition. 3 The Zn||Zn symmetric battery can stably cycle for 2250 h. Zn||V6O13 full battery achieved a capacity retention rate of 99.2% after 10,000 cycles.